Effectiveness of Mind Mapping Model Assisted by Pop-Up Book Media in Improving Students' Concept Understanding: Efektivitas Model Mind Mapping Berbantuan Media Pop-Up Book Dalam Meningkatkan Pemahaman Konsep Siswa - Utami, Retno; Ermawati, Diana; Ardianti, Sekar Dwi (Madrosatuna: Journal of Islamic Elementary School, 2024)
Understanding concepts is mastery of receiving and absorbing the material or information obtained. Based on the results of observations, it is known that students' understanding of concepts in science lessons in class V of SD 2 Demaan is still low. This research aims to increase students' conceptual understanding with a mind mapping learning model assisted by pop-up book media. This research is quantitative experimental research. This research was conducted in class V of SD 2 Demaan with 31 students as subjects. Data collection methods used include interviews, observation, tests and documentation. The results of the research obtained an average pretest score of 46.48 and an average posttest score of 88.06. Apart from that, this research also shows that the N-Gain value obtained is 0.77 in the high category. This shows that students' understanding of concepts after implementing the mind mapping model assisted by pop-up book media increased significantly and was effectively used in learning. Application of the mind map model with pop-up book media can increase understanding of concepts in the digestive system material in humans.